MODEL PENGEMBANGAN SOAL READING TOEFL BERBASIS TEKS-TEKS KEISLAMAN - IRWAN IRWAN (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2016)
Problem of this research is the unfamiliarity of the topics in TOEFL test. Many of the topics are talking about American and Europe. They are about American science, American history, American economic system, American culture and European culture. The topics above are not familiar to the students of State Islamic College because they seldom study about the topic. To answer the TOEFL tes it will be better for us to have background knowledge about the topics of the reading. If we are familiar with the topic, it will help us to be easy in answering and understanding about the text. This research used Research & Development (R&D) approach. The sample of the try out test for developing these questions are the sixth semester English students of STAIN Batusangkar. The data were analyzed by using Kappa model to differenciate the items difficulties, items differenciation, trapping model, validity and reliability. The product of this research then revised for three times. Then, the product is also commented and analyzed by the experts. After analyzing the revision of the product, the result finally getting ready to be used for a test.